Os significados do trabalho e as representações do consumo nas narrativas do eu: uma análise do projeto "Avon - Mémoria dos 50 anos de Brasil, no Museu da Pessoa - Bouéri, Fabio Sergio Teixeira (2011)
This research analyzes the narratives of the self published on the site and Museum of the Person-related multinational Avon. From the paper we analyze how labor and consumption are referenced in the speech of employees, former employees and dealers of cosmetics brand. They are subject to decode the organizational culture of the corporation, including the speeches relating to its products, to recode the construction of the meaning of life itself, a process which trajectory and attribute memory and elect the sphere of work as privileged mediation. To do so, we contextualize the object from the relationships between communication, work and consumption and the role of digital media in mediations and midiatizações subjects. In the research strategies of these narratives are applied foundations of discourse analysis in support of the French line in the examination of the corpus, whose content is the result of selection interviews. In this analysis, partial conclusions are presented on the way that the discourses of the interviewees are built and project a vision of the world related to Avon as a promoter of social meanings. The study also presents communication strategies deployed by the company, the Museum of the Person and by individuals to the constitution of the voices in order to give the speech a character of neutrality and legitimacy.